Hierarchical Analysis of Hypertension with the Polymorphic Variant of the ACE Gene and Other Risk Factors in the Elderly - Ribeiro,Breno Barreto (2017)
Abstract Background: Hypertension is a clinical condition of multifactorial etiology that imposes serious harm to the health of elderly individuals. Despite the fact that cardiovascular disorders influence the development of hypertension in this age group, several other genetic and environmental factors have been described in the literature, including the polymorphic variant of the angiotensin-converting enzyme (ACE) gene and the distribution of body fat. Objective: To assess the prevalence of hypertension among elderly individuals and its possible correlation with the I/D polymorphic variant of the ACE gene and other associated risk factors. Methods: Population-based study using a hierarchical model and including 387 elderly individuals residing in the urban area of Ibiaí (Minas Gerais, Brazil). Results: On statistical analysis, the polymorphic variant of the ACE gene was not associated with hypertension (p = 0.316). On the other hand, there was a significant association between hypertension and the variables female sex, absence of a partner, consumption of more than one portion of salt per day, and changes in body mass index and waist-to-hip ratio. Conclusion: Although the polymorphic variant of the ACE gene showed no influence on the prevalence of hypertension in elderly individuals, some variables such as individual, socioeconomic, metabolic, and behavioral habits were associated with this condition.